Level of Applying the Administrative Empowerment by the School Principals in Zarqa Governorate and its Relation with the Teachers’ Creative Behavior from their Point of View - Youssef, Murad Samhan (Journal of Educational and Psychological Sciences, 2022)
This study aimed to figure out the level of applying the administrative empowerment by the school principals in Zarqa Governorate and its relation with the teachers’ creative behavior from their point of view. To achieve the objectives of the study, the researcher used the descriptive, analytical approach as well as the questionnaire as a tool for data collection for a random sample of (205) male and female teachers in both the public and private schools in Zarqa Governorate. The study conclusions showed that the level of applying the administrative empowerment among the school principals in Zarqa Governorate from the teachers’ point of view was high; the mean of the level of applying the administrative empowerment was (3.87 out of 5) at the level of dimensions. The dimension of the power delegation obtained the highest average (3.98) followed by the effective communication with an average of (3.86), employees’ motivation with an average of (3.84), and finally training with an average of (3.79). All of which had a (high) level of application. The field of the teachers’ creative behavior in Zarqa Governorate from the teachers’ point of view had an average of (3.94 out of 5) with a (high) creative behavior at the level of dimensions. The dimension of the creative thinking obtained the highest average of (4.04) followed by the problem solution with an average (3.92) and finally the initiative and risk tolerance with an average of (3.86) and all of them had a high creative behavior. The study also found no statistically significant differences at sig. (α≤0.05) for the teachers’ opinions on the level of applying the administrative empowerment among the school principals or in the level of the creative behavior of teachers in Zarqa Governorate according to the variables of (gender, type of education, age, and educational qualification). Finally, the correlation value was (0.73) which referred to a strong direct and positive relation between the administrative empowerment and the teachers’ creative behavior in Zarqa Governorate. Based on the results of the study, the researcher recommends that the Jordanian Ministry of Education enhances the aspects of the administrative empowerment among the public and private school principals, and develop the creative behavior skills of teachers in the schools in Zarqa Governorate and throughout Jordan.